Business Strategy Development of Ruupa Id (Interior Design – Architecture Company) - Putra, Bhayu Tri Dita; Larso, Dwi (The Indonesian Journal of Business Administration, 2015)
The growth of the property business in Indonesia is growing very rapidly. According to data from Bank Indonesia in 2011 and 2012, the growth of property in Indonesia rose from 15% up to 38%. Besides residential housing property forms such as apartments, office buildings, and the shop is also growing very rapidly until today. Ruupa ID as a consultant and interior architecture workshop has the objective to be one of the leading consultants in Indonesia especially in Jakarta and Bandung. Ruupa ID established in December 2012. Ruupa ID’s first interior project is to design apartment in Jakarta. Ruupa ID has two different services and product department: service in design consulting and built-in furniture product making. Low brand awareness issue is one of problem that Ruupa ID faced today. Low marketing strategy and the customers rarely know about the company are the reason why Ruupa ID has low brand awareness. Business strategic development is a suitable tools for Ruupa ID business strategy. First step is by scanning internal analysis company about design uniqueness, team professionalism, and offering best quality to customers as strength and ineffective marketing campaign, lack of administration and marketing staff as the weaknesses of Ruupa ID. Based on the result of the Ruupa ID’s business plan analysis, the proposed business development strategy is divided into several steps, which are maximize the online and offline marketing campaign like website and social media; make standard operational procedure in every working process; make financial forecasting and hire new employee for financial and marketing department. Key Words: Interior Design, Architecture, Property, Built-in Furniture, Business Strategy.